The world-trade web: Topological properties, dynamics, and evolution - Giorgio Fagiolo; Javier Reyes; Stefano Schiavo (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2008)
This paper studies the statistical properties of the web of import-export relationships among world countries using a weighted-network approach. We analyze how the distributions of the most important network statistics measuring connectivity, assortativity, clustering and centrality have co-evolved over time. We show that all node-statistic distributions and their correlation structure have remained surprisingly stable in the last 20 years and are likely to do so in the future. Conversely, the distribution of (positive) link weights is slowly moving from a log-normal density towards a power law. We also characterize the autoregressive properties of network-statistics dynamics. We find that network-statistics growth rates are well-proxied by fat-tailed densities like the Laplace or the asymmetric exponential-power. Finally, we find that all our results are reasonably robust to a few alternative, economically-meaningful, weighting schemes.
Keywords: 330; Weighted Networks; World Trade Web; Distribution Dynamics; Power Laws; Econophysics; Internationale Wirtschaftsbeziehungen; Netzwerk; Statistische Methode